Immunological risk factors for nonalcoholic fatty liver disease in patients with psoriatic arthritis: New predictive nomograms and natural killer cells - Li, Baochen; Su, Rui; Yan, Huanhuan; Liu, Juanjuan; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Immunology, 2022)
Objective: To search for the immunological risk factors of Psoriatic arthritis(PsA) combined with nonal-coholic fatty liver disease(NAFLD), development and assessment of predictive nomograms for NAFLD risk in patients with PsA, and to further explore the correlation between risk factors and dyslipidemia. Methods: A total of 127 patients with PsA (46 with NAFLD and 81 without NAFLD) were included in this retrospective study. The clinical and serological parameters of the patients were collected. The percentage and absolute number of lymphocytes and CD4+T cells were determined by Flow cy-tometry. Univariate and multivariate binary logistic regression analysis was used to screen inde-pendent risk factors of PsA complicated with NAFLD in the model population, and a nomogram prediction model was developed and assessed. Results: (1) Univariate and multivariate logistic regression analysis of the modeling population showed that the percentage of peripheral blood T helper 1 cells (Th1%) (OR=1.12, P=0.001), body mass in-dex (BMI) (OR=1.22, P=0.005) and triglycerides (TG) (OR=4.78, P=0.003) were independent risk factors for NAFLD in patients with PsA, which were incorporated and established a nomogram prediction model. The model has good good discrimination and calibration, also has certain clinical application value. (2) The number of peripheral blood NK cells in PsA patients was significantly positively correlated with serum triglyceride(TG) (r=0.489,P<0.001), cholesterol (CHOL)(r=0.314,P=0.003) and low-density lipoprotein (LDL) (r=0.362,P=0.001) levels. Conclusions: Our study shows that the novel NAFLD nomogram could assess the risk of NAFLD in PsA patients with good efficiency. In addition, peripheral blood NK cell levels may be associated with dyslipidemia in patients with PsA.